Evaluation of Size of Public Sector in Malaysia - Ahmad, Halimah Nasibah; Noor Afza Amran,; Nor Laili Hassan, (IJRDO - Journal of Business Management, 2019)
There are two important sectors in a country, namely, the public sector and private sector. Unlike private sector, public sector is liable to ensure that there is an effective, efficient and economical utilization of public funds or resources to achieve the objectives of the government. Malaysian public sector was highlighted as having a large proportion of civil service compared to other countries in the world. Hence, the issue has triggered the researchers to conduct the current study. Generally, the objective of this study is to evaluate the size of public sector in Malaysia based on the percentage of total public sector expenditure to GDP. This study adopted a descriptive approach and data on public sector expenditure was retrieved from the Economic Reports produced by the Ministry of Finance from 1980-2017. From the evaluation, it can be concluded that the size of public sector in Malaysia was slightly bigger in 1980s compared to 1990s and 2000 onwards. The trend after 1986 was decreasing and became stable from 2000 onwards.